Mind Your Language Entrepreneur! Analysing Crowdfunding Success through the Lens of Effectuation Theory - Nuno Arroteia; Bibek Bhatta; Khalid Hafeez; Martin Quinn (Queen's University Belfast, Queen's Management School, 2021)
This research examines whether the adoption of narratives consistent with effectuation and causation in crowdfunding campaigns, impacts the likelihood of funders committing funds. The theoretical lens of effectuation are employed to examine the text narrative in a ten-year data set from kickstarter.com. The results support that narratives consistent with pre-commitments and means-orientation can have positive impact on the likelihood of successfully funding a campaign. Causal orientation positively impacts funding success in commercial campaigns, and negatively impacts funding of non-commercial campaigns. Our work expands the knowledge about how the narratives used by entrepreneurs in crowdfunding impact the funders' decisions to invest
Keywords: 330